Impacts of pH on leaching potential of elements from MSW incineration fly ash. (15th November 2016) - Zhang, Y.; Cetin, B.; Likos, W.J.; Edil, T.B.
Abstract: In this study, leaching behaviors of aluminum (Al), calcium (Ca), potassium (K), sodium (Na), barium (Ba), copper (Cu), manganese (Mn), zinc (Zn), arsenic (As), silver (Ag), chromium (Cr), cadmium (Cd), lead (Pb), selenium (Se), and sulfate (SO4 2− ) from fresh and aged municipal solid waste incineration (MSWI) fly ashes under different pH conditions (pH ∼ 2–14) were investigated. Results showed that majority of the elements followed a cationic leaching pattern where the leached element concentrations from fly ashes decreased with an increase in pH. Only Al, Ba, As, and Se showed different leaching patterns. Maximum concentrations of leached Al and As were measured at extreme acidic (pH ∼ 2) and basic (pH ∼ 12) conditions consistent with an amphoteric leaching pattern. Leached Se and Ba reached peak concentrations at very alkaline conditions (pH > 11) following an oxyanionic leaching pattern. Geochemical modeling analyses were conducted to determine controlling mechanisms of leaching of these elements. Leaching of elements, except As, Se, Ag, and Cr, were controlled by the dissolution/precipitation of their (hydr)oxides, carbonate or sulfate solids. Leaching of Cr may be controlled by BaCrO4(s), while no solid phases were found that controlled leaching of As, Se, and Ag. Sorption control leaching mechanisms should be included to determine the leaching mechanisms of these three elements. Leached element concentrations and leaching controlling mechanisms were not affected significantly by aging of the MSWI fly ash.